An exploratory study into energy consumption activities, energy-saving activities, and the factors that influence energy saving among Grade 7 children in Khayelitsha, Cape Town - Lusinga, Shanon (Energy Research Centre, 2018)
Energy is the engine that drives most human activity and is it very important today in the context of global warming and the high cost of energy. Yet there is limited research focusing on children's energy use in developing countries, including the ways in which they use energy, save energy and the factors that influence such activities. This is a serious deficit in energy literature and problematic because in the near future, today's children will make decisions about energy systems and climate change. This study gained insight into the ways in which Grade 7 children in Khayelitsha, Cape Town, use and save energy, and the factors that influence their energy saving. The study adopted a case study design, and mixed-methods approaches were used, including surveys, energy diaries, an interview and a focus group. The results show that children in Khayelitsha demonstrated a broad understanding of the concept of energy including topics on the environment, basis of life and thermal energy. The children displayed understanding of broader socio-economic, environmental and health issues as they were cognisant of national and community issues, such as limited energy access and the dangers of indoor use of coal. They had lower scores on more abstract and technical topics such as energy transitions and differentiating between renewable and non-renewable sources on energy. 86% of the children in this study acknowledged the importance of saving energy, while more than 50% failed to recognise the importance of caring for the environment and moving away from fossil fuels. The study results show that children use multiple sources of energy at home and that the majority of their energy activities were performed at home, followed by school and church. The children reported several energy consumption activities including cooking for others, using the kettle for bathwater and ironing their clothes - findings contrary to activities reported by children in developed countries. For some of the children, the results suggest that energy use may be accompanied by guilt as children want to reduce financial pressures at home, a finding consistent with existing literature. Energy-saving activities included switching off and removing appliances from the wall plug. Children were found to be motivated to save energy by several factors, of which financial considerations were the most dominant. The children demonstrate altruistic tendencies, as motivation to save energy seems to be influenced by the desire to help their families and communities. The study further identified that parents, the community, the school, peers and the relationship between the school and government departments had either a direct or an indirect influence on children. Parents with a positive attitude towards energy saving and the environment were more likely to talk to their children about energy saving, which tended to focus on related financial issues. A conceptual framework is presented to analyse the data, which incorporates existing psychological and sociological frameworks and theories used to explain energy behaviour in addition to theories on child development.